Numerical Investigation on Pressure Pulsation Characteristics and Radial Force of a Deep-Sea Electric Lifting Pump at Off-Design Conditions - Yajuan Kang; Shaojun Liu; Weisheng Zou; Xiaozhou Hu (Shock and Vibration)
To predict the vibrational conditions, the generation mechanism, and action law of pressure pulsation and radial force, a computational fluid dynamics (CFD) study of a deep-sea electric lifting pump operating under different off-design conditions was performed. The time-domain and frequency-domain response of the pressure pulsation at different monitoring points and the radial force of impeller distribution were obtained. Differences in pressure pulsation characteristics between the first stage and second stage were observed. The variation law and influential factors of the radial force under different flow rates were discussed. The present investigation shows that the flow field caused by rotor-stator interaction is not uniform, resulting in uneven pressure distribution and pressure pulsation, the combined effects of which produce fluctuating radial forces. Parameters obtained via simulations including head, efficiency, and power, which can reflect the hydraulic performance of the pump, agree well with experimental results; thus, the accuracy of the simulation model and the calculation method was verified. This study provides a basis for improving the structure and reliability of an electric lifting pump.